Efecto de diferentes densidades de siembra en el rendimiento de Caupi (Vigna unguiculata (L) walp) en el Bajo Mayo - Sánchez Gil, Nelida (1994)
In order of White to determine the optimum density of sowing of white Caupea beans line CNCX-0434, for ecological conditions of Bajo Mayo área. This work has been written between September and December, 1991.in the estación. Experimental “El Porvenir'', Distrito Juan Guerra, Provincia 1 Región San Martín, located at 6º34' south latitud, 76°20 west latitud and 230 meters over sea level, with an annual overage temperature of 26.21ºC and an annual average rainfall of 994.04 m.m. The ground shows the following characteristics clay texture; pH 6.1; available phosphorus 9 ppm; available potassium 202 ppm ;: organic: material 3.5% calcitum 16.77 meq/100g of ground ; magnesium 2.2meq/100g of ground. He stadistic design that was followed is the complete lock at random in divided plots with 04 repetitions, 16 reatments and 64 experimental ones. It was tested, percentage of germination, heigh of plantation, plantation covering, flowering days, number of plantation crops, number of pods per plantation, number of rains per pod, pods size, weight of 100 seeds, efficiency f produce per hectare (Kg/Há).